Efficacy and safety of sodium hyaluronate combined with celecoxib for knee osteoarthritis: A systematic review and meta-analysis - Mengjie Zeng; Zhiquan Wu; Jinying Liang; Aimin Gong (Asian Journal of Surgery, 2024)
Due to the large cost of joint replacement for surgical treatment of knee osteoarthritis, there are many complications in elderly patients, and there are many contraindications to surgery, and conservative treatment is still based on drugs. To further evaluate the efficacy and safety of sodium hyaluronate combined with celecoxib for the treatment of osteoarthritis of the knee. In total, 202 studies were screened, with a final selection of 9 RCTs involving 2339 participants; of these, 9 RCTs were included in the final meta-analysis. Treatment group reduces VAS (SMD = −1.61; 95 % CI [−2.25, −0.98]; I2 = 95 %; P < 0.00001) and adverse reactions (OR = 0.45; 95 % CI [0.22,0.94]; I2 = 0 %; P < 0.33); Meanwhile, improving Lysholm knee scores (SMD = 0.19; 95 % CI [−0.06, −0.44]; I2 = 76 %; P = 0.0004) and Clinical efficiency (OR = 0.31; 95 % CI [0.19,0.50]; I2 = 0 %; P < 0.00001). All indicators were superior to the control group. Our primary findings suggest that KOA treatment with celecoxib combined with sodium hyaluronate reduces VAS, while improving Lysholm scores and Clinical efficiency. In addition, we found that celecoxib combined with sodium hyaluronate treatment had fewer adverse effects than the control group, indicating that the combination is safe and effective in the treatment of KOA.